2013
DOI: 10.1179/1743285513y.0000000041
|View full text |Cite
|
Sign up to set email alerts
|

Carbothermic reduction of Zambian sulphide concentrates in presence of lime

Abstract: The investigation focuses on an alternative route to metallic phase extraction from complex Zambian copper-cobalt sulphide mineral concentrates, derived from the Copperbelt region. In the context of developing a novel process route for metal extraction without sulphur dioxide emission and slag waste generation, we have studied the reduction of copper-cobalt sulphide concentrates via carbothermic reduction in the presence of lime by following the equilibrium: MSzCaOzC5MzCaSzCO(g), where M represents the metalli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…In this study, the other possibility is reduction of FeO via Eqs. (3) and/or (9) followed by carbon gasification via the Boudouard reaction according to Eq. (7) which causes a larger weight loss than the stoichiometric weight change.…”
Section: Effect Of Microwave Heating On Reduction Degreementioning
confidence: 99%
See 1 more Smart Citation
“…In this study, the other possibility is reduction of FeO via Eqs. (3) and/or (9) followed by carbon gasification via the Boudouard reaction according to Eq. (7) which causes a larger weight loss than the stoichiometric weight change.…”
Section: Effect Of Microwave Heating On Reduction Degreementioning
confidence: 99%
“…1) Lime (CaO) has a high tendency for reaction with sulfur to form CaSO 4 and CaS in the oxidizing and reducing atmosphere, respectively. 2,3) Hara et al 3) reported the production of Cu, Co and Fe after a carbothermic reduction of sulfide concentrate containing copper, cobalt, and iron in the presence of CaO at 1 000°C. Also, Hara et al 4) has studied the reduction of a mineral sulfide-CaO-C mixture and demonstrated that an increase in mole ratio of C:CaO improves magnetic separation of products into metal and CaS.…”
Section: Introductionmentioning
confidence: 99%
“…The carbothermic reduction and sulphidization experiments were carried out isothermally, in the thermogravimetric analysis (TGA) equipment, in order to study the weight loss as a function of time. Details of the thermogravimetric analysis equipment are found in our previous studies [19,20]. The reaction chamber was purged with argon gas at a flow rate of 0.6 litre min -1 , for maintaining inert atmosphere [19].…”
Section: Reduction and Sulphidization Experimentsmentioning
confidence: 99%
“…The phases in the powder diffraction patterns were analysed by the X'pert high score plus software which is supported by the JCPDS PDF-4+ data base (RDB 2013) [20].…”
Section: X-ray Powder Diffraction Analysismentioning
confidence: 99%
“…Reduction of sulfide minerals in the presence of lime (CaO) has been studied in previous literature [1,2] . Hara et al [1] produced metallic Cu, Co and Fe from a sulfide concentrate via a carbothermic reduction in the presence of CaO at 1000 °C. Jha et al [3] showed that the reduction of FeS:CaO:C = 1:1:2 mixture initiates after a heat treatment at 850 °C for > 90 min.…”
Section: Introductionmentioning
confidence: 99%